Using task based learning to improve junior high school speaking skill on procedure text - Pabriana, Handi; Muziyawanti, Meily; Megawati, Anisa Septia; Jeni (International Journal of Advances in Educational Research, 2025)
This study evaluates the efficacy of Task-Based Learning (TBL) in enhancing students’ English speaking proficiency, particularly in delivering procedure texts, and identifies the most pronounced pronunciation improvement. Conducted at SMP Negeri 1 Cikakak, ninth-grade students were randomly assigned to an experimental class using TBL or a control class receiving conventional instruction. The speaking assessment evaluated fluency, accuracy, pronunciation, and idea organization. This study addresses the research gap by analyzing pronunciation aspects, unlike previous studies that focused solely on TBL for teaching procedure texts at the junior high school level. The experimental class showed a substantial improvement, with a mean score surge from 57.80 to 80.50, while the control class experienced only a modest improvement from 55.67 to 62.33. The N-Gain score of 51.94 for the experimental group was effective, while the control group’s gain of 14.06 was ineffective. Statistical tests confirmed a significant disparity between the groups. Students also showed a favorable response to the TBL method, supporting the assertion that TBL effectively enhances speaking skills and engages students in learning.